(untitled) - Williamson, Kenneth L. (Lexington, Mass, 1994)
This is book continues to be the only organic chemistry laboratory manual is which virually all of the experients are presented on both a macroscale and a microscale.
Keywords: Chemistry, Organic,Hóa học, vô cơ